PENGELOLAAN ARSIP DINAMIS DI KANTOR BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL (BKKBN) PROVINSI SULAWESI UTARA - RIZKY WALANGADI; FEMMY TULUSAN; HELLY KOLONDAM (Sam Ratulangi University, 2022)
ABSTRACTThe purpose of this study was to determine the management of dynamic archives at the office of the National Population and Family Planning Agency (BKKBN) of North Sulawesi Province. This research uses descriptive qualitative research is management. Sources of data used in this study are primary data and secondary data with data collection techniques namely observation, interviews and documentation. The theory used is the theory of Agus Sugiarto and Teguh Wahyono (2005) with five factors for the implementation of archive management. Based on the results of the study, it was shown that the National Population and Family Planning Agency (BKKBN) of North Sulawesi Province had not fulfilled significantly as a whole. As for the findings of the study, it is known that ini quantity archivist employees only seve as functional, there is no special budget, the equipment and facilities are not fully adequate, and the dynamic archive arrangement system is not optimal as a whole. In finding the archives again. The suggestions from the researcher are that Human Resources (HR) should be optimized again regarding the number of archive employees, there must be a special budget for managing archives, it is necessary to provide archive storage tools, socialize digital storage related to the one-heart application, and reorganize the archive arrangment. Dynamic in fields and offices.Â Â Keywords : Management, Dynamic Archives